UJI EFEKTIVITAS PEMBERIAN PACLOBUTRAZOL TERHADAP KESEIMBANGAN PERTUMBUHAN TIGA VARIETAS KACANG TANAH (Arachis hypogaea L.) - Nova Chrisnauli Simanjuntak; Eva Sartini Bayu; Isman Nuriadi (Universitas Sumatera Utara, 2013)
Paclobutrazol Application Study on Balance the Growth of Three Varieties of Peanuts(Arachis hypogaea L.). This study aimed to learn effect of paclobutrazol application ongrowth of three varieties of peanuts. The research was conducted at Tanjung Sari, Medan (±25 m above sea level) from June – October 2012 used randomized block design. The firstfactor was the paclobutrazol concentration with 4 level were 0, 100, 200 and 300 ppm and thesecond factor was three varieties were Gajah, Bima and Domba with 3 replication. Parameterwere plant length, number of productive branch, flowering time, harvest time, ginofornumber formed per sample, number of pod contains, seed weight per sample and weight of100 seeds. The results showed that paclobutrazol significant of plant length 7-9 week afterplant. Variety significant of plant length 2-9 weeks after plant, number of productive branchat 5-9 weeks after plant, flowering time, harvest time, ginofor number formed per sample,weight of 100 seeds, but not significant to number of pod contain and seed weight persample. Whereas, interaction between paclobutrazol and varieties only significant to reducenumber of empty pods.Keywords: peanuts, paclobutrazol, varieties